Peran Brand Ambassador K-Pop terhadap Keputusan Pembelian Konsumen: Studi pada Produk Nabati dan Komunitas MYNE - Isna Masmira Dwijayanti; Indah Respati Kusumasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to evaluate the influence of aespa, appointed as a brand ambassador, in increasing Nabati’s purchasing decisions among the MYNE community using the VisCAP method. The method applied in this research is quantitative. A quantitative approach allows data to be collected in numerical form and analyzed using various statistical methods, such as descriptive analysis to illustrate data characteristics, correlation analysis to identify relationships between variables, and hypothesis testing to examine differences or associations within the data. This process enables researchers to identify patterns, trends, or influences that can be applied to larger populations. The sampling technique is divided into two categories: non-probability sampling and probability sampling. Data for this research were obtained by distributing questionnaires to respondents who are members of the aespa fan community (MYNE), and data collection was also supported by a literature review. The variables examined in this study are Brand Ambassador as variable X and Purchase Decision as variable Y. The data analysis techniques used include validity and reliability tests, classical assumption tests, hypothesis testing, and simple linear regression analysis. Findings from the t-test on variable X (Brand Ambassador) show a t-value of 7.316 with a significance level of 0.000. Since the significance value is below 0.05 (0.000 < 0.05) and the regression coefficient is positive at 0.701, it can be concluded that the brand ambassador has a 70.1% influence on consumers’ purchasing decisions.